An alternative recommendation for design eccentricity by consideration of uncoupled frequency ratio - Osman Akyürek; Hakan Ulutaş (Scientific Reports)
Abstract Civil structures are prone to dynamic loadings such as strong winds or ground excitations where torsion becomes an ongoing issue. This arises from a lack of coincidence of the center of mass (CM) and rigidity (CR), known as eccentricity. Seismic design codes often introduce two types of eccentricity: inherent (geometric) and accidental. To account for structural or ground motion uncertainties, an assumption-based solution is provided by many code provisions, which considers the accidental eccentricity as a percentage (5% or 10%) of the building length perpendicular to the direction of exposed ground motion. In this study, as an alternative way to the code design parameters, a new design eccentricity formula that considers the frequency ratio (torsional frequency/translation frequency) and an effective radius of gyration to account for torsional irregularity is considered. For the extended validation of the proposed method, eighteen model buildings with six different floor plans were chosen, representing low, medium-height, and high-rise buildings. Each floor plan had model buildings with three, seven, and twelve stories. The buildings were subjected to selected bidirectional earthquake ground motions and had time history analyses performed. The results of the proposed method were compared to code provision methods, obtained using equivalent lateral force procedures, and also to those obtained utilizing the time history analysis results. It was shown that the proposed method was more effective in estimating the impact of torsional eccentricity and provided a better understanding of its impact on structural dynamic characteristics.